Nutrition, obesity and hormones - Marco Giammanco; Laura Lantieri; Gaetano Leto; Fulvio Pescia; Danila Di Majo (Journal of Biological Research, 2018)
Obesity is a chronic pathological condition with a multifactorial aetiology, characterised by an excessive body fat accumulation with multiple organ-specific consequences. Emerging evidence highlights that obesity appears to be associated with multiple alterations in the endocrine system. However, the mechanisms underlying the interactions between obesity and this system remain still controversial. This review discusses the impact of obesity on various endocrine systems and, in particular, would provide a general overview on the biochemical changes that may occur in each of these axes in association with obesity.